2015
DOI: 10.1002/jaba.263
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of choice on instructional efficacy and individual preferences among children with autism

Abstract: The current study compared the differential effects of choice and no-choice reinforcement conditions on skill acquisition. In addition, we assessed preference for choice-making opportunities with 3 children with autism, using a modified concurrent-chains procedure. We replicated the experiment with 2 participants. The results indicated that choice-making opportunities increased treatment efficacy for 2 of the 3 participants, and all 3 participants demonstrated a preference for choice-making opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 22 publications
3
42
2
Order By: Relevance
“…The concurrent chains procedure described by Hanley et al () has since been adopted as a method to objectively assess participant preference for behavioral intervention and has been applied to assess preference among a variety of interventions (DeLeon et al, ; Fienup, Ahlers, & Pace, ; Luczynski & Hanley, ; Toussaint, Kodak, & Vladescu, ). Additionally, several researchers have suggested that when treatment effects of two or more interventions produce similar outcomes, participant preference should be considered in ultimate treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The concurrent chains procedure described by Hanley et al () has since been adopted as a method to objectively assess participant preference for behavioral intervention and has been applied to assess preference among a variety of interventions (DeLeon et al, ; Fienup, Ahlers, & Pace, ; Luczynski & Hanley, ; Toussaint, Kodak, & Vladescu, ). Additionally, several researchers have suggested that when treatment effects of two or more interventions produce similar outcomes, participant preference should be considered in ultimate treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The literature includes reports of a number of mastery criteria such as 80% correct for a single session (McCormack, Arnold‐Saritepe, & Elliffe, ), 80% correct across two or three sessions (Najdowski et al, ), 90% correct across two sessions (Toussaint, Kodak, & Vladescu, ), 90% correct across three sessions (Wunderlich & Vollmer, ), 100% for a single session (Grow, Kodak, & Clements, ), and 100% across three sessions (Belisle, Dixon, Stanley, Munoz, & Daar, ). Mastery criteria vary across multiple dimensions including percentage correct, number of sessions/trials, and additional variables such as applying those criteria across multiple therapists, to name a few.…”
mentioning
confidence: 99%
“…Treatment preference was evaluated using a concurrent chains design by having each participant select the method used to teach the functional skill (i.e., prose self‐instruction, song lyric self‐instruction). The experimenter presented two cards with the words “say” and “sing” printed on them and asked each participant to choose their preferred teaching method, based on procedures described by Hanley () and Toussaint, Kodak, and Vladescu (). However, rather than presenting the opportunity to choose at the beginning of each session, participants were only provided one opportunity to choose the self‐instruction procedure.…”
Section: Methodsmentioning
confidence: 99%